2014
DOI: 10.1093/glycob/cwu125
|View full text |Cite
|
Sign up to set email alerts
|

Insect trehalase: Physiological significance and potential applications

Abstract: Trehalose, a non-reducing disaccharide, is widespread throughout the biological world. It is the major blood sugar in insects playing a crucial role as an instant source of energy and in dealing with abiotic stresses. The hydrolysis of trehalose is under the enzymatic control of trehalase. The enzyme trehalase is gaining interest in insect physiology as it regulates energy metabolism and glucose generation via trehalose catabolism. The two forms of insect trehalase namely, Tre-1 and Tre-2, are important in ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
245
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(253 citation statements)
references
References 76 publications
5
245
0
1
Order By: Relevance
“…One particular disaccharide, trehalose, is a glucose-glucose disaccharide linked by an α,α, 1,1-glycoside bond. Trehalose is ubiquitous to a wide variety of organisms, including bacteria, yeast, fungi, insects, and invertebrates, but trehalose is absent in vertebrate animals (8). .…”
Section: Introductionmentioning
confidence: 99%
“…One particular disaccharide, trehalose, is a glucose-glucose disaccharide linked by an α,α, 1,1-glycoside bond. Trehalose is ubiquitous to a wide variety of organisms, including bacteria, yeast, fungi, insects, and invertebrates, but trehalose is absent in vertebrate animals (8). .…”
Section: Introductionmentioning
confidence: 99%
“…However, previous experiments on blow flies have demonstrated that the availability of trehalose -the disaccharide of glucose in insects -is a limiting factor for the duration of flight performance (Clegg and Evans, 1961). Trehalose is the primary blood sugar in insects and it plays a major role in insect flight, acting as the source of instant energy as well as mitigating abiotic stressors (Shukla et al, 2015). Synthesized by the fat body, trehalose is hydrolysed by the trehalase enzyme, releasing glucose into the flight muscle (Becker et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…TRE1 and TRE2 are known to regulate wing development, light metabolism, and chitin biosynthesis1320. The chitin biosynthesis pathway involves eight enzymes, namely TRE, hexokinase (HK), glucose-6-phosphate isomerase (G6PI), fructose-6-phosphate transaminase (GFAT), glucosamine-phosphate N-acetyltransferase (GNPNA), phosphoacetylglucosamine mutase (PGM), UDP-N-acetylglucosamine pyrophosphorylase (UAP), and chitin synthase (CHS), and is crucially important for insect life2627282930.…”
mentioning
confidence: 99%